Prevalence of performance-enhancing drug use among gym members in Saudi Arabia, Riyadh: A cross-sectional survey - Eskandarani, Rawan; Alhamad, Abdulaziz; Almodameg, Saad (Journal of Sports Medicine and Therapy, 2022)
Context: Illicit and performance-enhancing drug (PED) use is prevalent among athletes. Aims: We examine the prevalence of PED use among amateur athletes, identify the common characteristics and associated risk factors for illicit PED use and measure the perception and awareness among gym members regarding the safety and effects of illicit drug use. Settings and design: This cross-sectional study was conducted among adult male and female gym center attendees in Riyadh, Saudi Arabia. Methods and materials: Self-administered Arabic and English questionnaires were used for data collection. Statistical analysis used: SPSS version 26 was used to perform t- and chi-square tests. Results: This study included 379 participants, of whom 59.6% were male, 52.8% were between 26 and 35 years of age, and a majority of the participants had normal (47.5%) or overweight (40.9%) body mass index. Our study revealed a high prevalence (48.5%) of PED use among gym athletes in Riyadh, Saudi Arabia. Moreover, the true prevalence might have been higher due to the possibility of underreporting by some participants because of the sensitivity of the subject. Protein powder was the most commonly used type of PED. Of all the participants, 22.3% reported anabolic androgenic steroid use. Side effects of PEDs were observed in 19% of the study participants. Conclusion: The results of this study should encourage public health researchers and health advocates to design and implement behavioral interventions to educate the public on the benefits, risks, and contraindications of dietary supplements used by athletes to enhance their body performance. Key messages Performance-enhancing drug (PED) use is prevalent among both professional and amateur athletes. Gym athletes in Riyadh, Saudi Arabia, report increasing PED use. Side effects and negative health impacts are associated with illicit PED use. Misinformation on the risks and benefits of PEDs is a major public health concern. More efforts should be implemented in public awareness about the risk of using PED targeting younger populations.